Effects of Light and Sound on the Prefrontal Cortex Activation and Emotional Function: A Functional Near-Infrared Spectroscopy Study - Hori, Shota; Mori, Koichi; Mashimo, Takehisa; Seiyama, Akitoshi (Frontiers in Neuroscience, 2017)
We constructed a near infrared spectroscopy-based real-time feedback system to estimate the subjects’ emotional states using the changes in oxygenated hemoglobin concentration ([oxy-Hb]) in the prefrontal cortex (PFC). Using this system, we investigated the influences of continual mild and equivocal stimuli consisting of lights and a reconstructed waterfall sound on [oxy-Hb] in the PFC. The visual (light) and auditory (sound) stimuli changed randomly and independently, depending on the emotional states of the individual subjects. The emotional states induced by the stimuli were examined via a questionnaire rated on an 11-point scale, from +5 (pleasant) to ˗5 (unpleasant), through 0 (neutral), after the 5-min experiments. Results from 757 subjects revealed that [oxy-Hb] in the PFC exhibited a weak, but significant, correlation with emotional change, with the given continual and mild stimuli similar to that experienced in response to the intense pleasant/unpleasant stimuli. Based on the results we discuss the generation of pleasant/unpleasant weak emotional change induced by mild and weak stimuli such as light and sound.